Comparing rheological, tribological and sensory properties of microfibrillated cellulose dispersions and xanthan gum solutions. (December 2021) - Blok, Annelies E.; Bolhuis, Dieuwerke P.; Kibbelaar, Heleen V.M.; Bonn, Daniel; Velikov, Krassimir P.; Stieger, Markus
Abstract: Utilisation of plant waste materials contributes to sustainable food production and allows preparation of functional ingredients from natural bio-materials. Microfibrillated cellulose (MFC) from plant waste materials such as citrus peels has been suggested to have potential as "clean label" thickener. This study compared rheological (shear and extensional rheology, hysteresis, yield stress), tribological and sensory properties of MFC dispersions (0.2–2.0 wt%) to xanthan gum (XG) solutions (0.04–4.3 wt%) and linked sensory characteristics to instrumental properties. Concentrations of MFC and XG were chosen so that shear viscosities of MFC dispersions and XG solutions were similar over a large range of shear rates. XG had higher extensional viscosity at high deformation rates than MFC. XG had higher yield stress than MFC at similar shear viscosity. Yield stress increased linearly with increasing concentrations for XG, while it increased exponentially for MFC. Seventy-three consumers evaluated the appearance, flavour, and mouthfeel of all samples using the Rate-All-That-Apply (RATA) method. Sensory differences between MFC and XG were generally larger at higher concentrations. MFC dispersions were less transparent and had more intense cardboard flavour than XG solutions of comparable shear viscosity. At high thickener concentrations, XG solutions were perceived as glossier, stickier, slimier and more mouthcoating than MFC dispersions of similar shear viscosity. Sticky, slimy and mouthcoating perception were correlated with extensional viscosity at higher deformation rates. We conclude that MFC can thicken foods similar to XG while avoiding undesired texture sensations such as mouthcoating, sliminess and stickiness. The flavour and dispersibility of MFC need to be improved further before it can be applied as thickener in foods. Graphical abstract: Image 1 Highlights: Comparison of microfibrillated cellulose (MFC) and xanthan gum (XG) in water. XG had higher yield stress than MFC at similar shear viscosity. Extensional viscosity of XG at high deformation rates was higher than that of MFC. XG solutions were perceived stickier, slimier and more mouthcoating than MFC dispersions at comparable thickness. Sticky, slimy and mouthcoating perception are correlated with extensional viscosity.